Framework Administered Account for Selected Fund Activities : Middle East Regional Technical Assistance Center (METAC) Subaccount. (Policy Papers; Policy Paper ;, 2009)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the "SFA Instrument"). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. This paper requests Executive Board approval to establish the METAC subaccount under the terms of the SFA Instrument. Management has engaged in discussions with member countries in the Middle East region as well as donors on regional needs in capacity building, training and related activities. Because METAC has a proven track record to provide focused, flexible, and responsive technical assistance (TA) in a cost-effective manner, both beneficiary countries of METAC and interested donors are supportive to continue the Fund's involvement in this regard. The center's activities will continue to focus on the following key areas representing common policy challenges to member countries, including those related to increased regional integration: (i) revenue administration; (ii) public financial management; (iii) banking supervision; and (iv) economic and financial statistics.